2011
DOI: 10.1021/jp200465n
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition of Hierarchical Micro/Nanostructures of Copper Hydroxysulfates on Polypyrrole−Polystyrene Sulfonate Films

Abstract: Copper-based hierarchical micro/nanostructures were prepared using a novel electrochemical route on polypyrrole−polystyrene sulfonate (PPy−PSS) thin films. The resulting structures are composed of copper hydroxysulfates, as confirmed by the electrochemical, spectroscopic, and X-ray diffraction characterization. The electrochemistry of the film is a key factor in the overall deposition of the micro/nanostructures. The PPy−PSS films capture cations from the copper sulfate electrolyte solution and facilitate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…Two peaks at 531.6 and 533.6 eV are found from the deconvolution of the signal. The peak at 531.6 eV can be attributed to the O=S of the dopant present in the PPy/ASPB nanocomposite [32], while the peak located at 533.6 eV may be related to the oxygen contribution of bound water and polymer-oxidized moieties. XPS studies indicate that doping of ASPB into PPy matrix is achieved, as expected, which is consistent with both FTIR studies.…”
Section: Xps Studymentioning
confidence: 99%
“…Two peaks at 531.6 and 533.6 eV are found from the deconvolution of the signal. The peak at 531.6 eV can be attributed to the O=S of the dopant present in the PPy/ASPB nanocomposite [32], while the peak located at 533.6 eV may be related to the oxygen contribution of bound water and polymer-oxidized moieties. XPS studies indicate that doping of ASPB into PPy matrix is achieved, as expected, which is consistent with both FTIR studies.…”
Section: Xps Studymentioning
confidence: 99%
“…This fractal geometry in electrochemical cells increases the electrochemically active surface area by decreasing the transport energy lost inside the network. Andreoli et al (2011) studied the electrodeposition of hierarchical micro/nanostructures of copper hyroxysulfates on thin film of polypyrrole-polystyrene sulfonate. Some researchers have reported the work of copper fractal on polypyrrole doped with different anions (Sakar, Zhou, Tannous, & Leung, 2003;Cioffi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by our group has shown that copper-based hierarchical micro/nanostructures could be deposited on a polypyrroleÀpolystyrene sulfonate (PPyÀ PSS) film from aerated or oxygen-saturated CuSO 4 solutions at a potential of 0.10 V vs SCE. 37 The structures were fully characterized and found to consist of a mixture of two different copper hydroxysulfates…”
Section: ' Introductionmentioning
confidence: 99%
“…39 The copper-based micro/nanostructures were formed electrochemically on the surface of the PPyÀPSS films. 37 After the electropolymerization, the electrodes were thoroughly rinsed with Milli-Q water and immersed in 0.10 M CuSO 4 aerated or oxygensaturated solution. The potential of the electrode was set at a constant value of 0.10 V vs SCE until a certain charge was passed (usually 40 mC/cm 2 ), and the copper-based structures were formed.…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation